Bust of Steinbeck - Jesse Wallace Corsaut:::Creator::::::::::::
Bust of Steinbeck in his mid forties. This bust was done long after Steinbeck died and this figure was used as a model to create the current Steinbeck "In the Soul's of the people" award. Jesse Wallace Corsaut is the artist who later did the Presidential Medallion for Bill Clinton.